Diversidad, estructura y concentración de carbono en un bosque siempreverde piemontano de 800 a 900 msnm, en la Amazonía Ecuatoriana - Torres Navarrete, Víctor Alfredo (2016)
The objective of the present research was to evaluate the structure, diversity and carbon storage in an evergreen old-growth piemontano forests at north-center of the Eastern Andes from 800 to 900 masl, in the Ecuadorian Amazon. For which five permanent 100 m x 10 m sampling transects were implemented. The study included 385 individuals’ trees with DBH ≥ 10 cm, represented by 38 genera, 72 species. The Arecaceae, Moraceae, Myristicaceae, Lauraceae, Urticaceae, Annonaceae, Meliaceae, Rubiaceae and Clusiaceae were the families with the greatest number of species. The results of floristic diversity using Shannon Indexes (3.71) and the Simpson index (0.95) reveal that this evergreen forest of the Napo foothill has a diverse floristic composition and there is dominance of few species. The families with the highest index of importance by family (IVIF) were: Moraceae 11.66%, Myristicaceae 8.89%, Arecaceae 7.11%, Unidentified 6.71%, Lauraceae 5.36%; And families with lower IVIF: Piperaceae, Sapindaceae 0.47%, 0.59%, Malvaceae, Araliaceae 0.46% among others, the species with the highest IVI were: Unidentified 15.68%, Otoba glycycarpa 6, 42%, Ficus sp., 6.08%, Iriartea deltoidea 5.91%, Nectandra sp., 3.92%, Virola sp., 3.92% and the species with lower IVI: Eugenia sp., Quararibea sp., Mabea sp., 0.37%. The Moraceae family, third in abundance of individuals with a presence of 8.83% as a total of individuals contributes with 23.82% of the carbon stored in the forest of the study area. It is recommended to develop specific research on structure, diversity and carbon concentration in the different types of forests that exist in mainland Ecuador, as well as in its different altitudinal gradients, in order to have better information for decision making in the forest management utilization and conservation of the Andean-Amazon Ecuadorian tropical forests.